Giáo trình Luật Lao động Việt Nam - Nguyễn, Hữu Chí; Trần, Thị Thúy Lâm; Đỗ, Ngân Bình; Đỗ, Thị Dung; Đoàn, Xuân Trường; Hà, Thị Hoa Phượng; Hoàng, Thị Minh; Nguyễn, Hiền Phương (Công an Nhân dân, 2022)
Gồm 10 chương: Khái niệm luật Lao động Việt Nam; Quan hệ pháp luật lao động; Đại diện các bên trong quan hệ lao động;...